In Memory Data Management and Analysis: First and Second International Workshops, IMDM 2013, Riva del Garda, Italy, August 26, 2013, IMDM 2014, Hongzhou, China, September 1, 2014, Revised Selected Papers - Jagatheesan, A (Springer, 2015)
This book constitutes the thoroughly refereed post conference proceedings of the First and Second International Workshops on In Memory Data Management and Analysis held in Riva del Garda, Italy, August 2013 and Hangzhou, China, in September 2014. The 11 revised full papers were carefully reviewed and selected from 18 submissions and cover topics from main-memory graph analytics platforms to main-memory OLTP applications.